2021
DOI: 10.1134/s2079057021030115
|View full text |Cite
|
Sign up to set email alerts
|

Why Older People Seek Health Information Online: A Qualitative Study

Abstract: Despite the increasing number of older adults’ growing need for health information, little is known about their motivation to seek online health information. This exploratory qualitative study was conducted to examine why older adults seek required health information through online sources. In this qualitative content analysis, we purposefully approached 19 older adults with age in the range between 60–75 (63.78 ± 3.8 years) in Tabriz, Iran. Data were collected via individual, semi-structured face-to-face inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Based on a previous study [38], we identified the variables that were used to measure the health information-seeking behavior, namely, (1) self-efficacy for online information seeking, (2) perceived encouragement, (3) positive attitude toward e-HISB, (4) perceived usefulness, (5) challenges of being visited by physicians, and (6) online-seeking inhibitors and perceived barriers to e-HISB. A 5-point Likert-type scale (1 = strongly disagree; 5 = strongly agree) was used to measure the motivators and inhibitors of the e-HISB; the negatively stated items were reverse-coded.…”
Section: Methodsmentioning
confidence: 99%
“…Based on a previous study [38], we identified the variables that were used to measure the health information-seeking behavior, namely, (1) self-efficacy for online information seeking, (2) perceived encouragement, (3) positive attitude toward e-HISB, (4) perceived usefulness, (5) challenges of being visited by physicians, and (6) online-seeking inhibitors and perceived barriers to e-HISB. A 5-point Likert-type scale (1 = strongly disagree; 5 = strongly agree) was used to measure the motivators and inhibitors of the e-HISB; the negatively stated items were reverse-coded.…”
Section: Methodsmentioning
confidence: 99%
“…However, although the current literature offers insight into factors influencing online health information seeking of older adults, few of the prior studies have yet clarified the influence mechanism (24). Improving the online seeking behavior of older people is more difficult than that of younger people because of cognitive limitations, low electronic health literacy, and negative attitudes toward technology (6).…”
Section: Online Health Information Seeking Of Older Adultsmentioning
confidence: 99%
“…This paper will examine the issue of regulation of smart aging platforms from the perspective of privacy breaches. For the elderly, they can act as supervisors, pursuing reasonable prices for the operation and services of the wisdom aging platform, diversification of service types, as well as focusing on the experience of the platform services, which are the main sources of revenue for the platform [31]. As beneficiaries of the wisdom aging platform, their interest is to bring convenience and spiritual and emotional comfort to their lives through the aging platform's services.…”
Section: Application Scenariomentioning
confidence: 99%